PENERAPAN PENDEKATAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VII MTs PADA MATERI PERBANDINGAN DAN SKALA - Ratna Marlina; Sifa Nurjahidah; Asep Ikin Sugandi; Wahyu Setiawan (IKIP Siliwangi, 2018)
This research aims to get results description of application of problem based learning approach in an effort to enhance student learning outcomes as well as knowing the increase in mathematical problem solving ability grade VII MTs on comparison of material and scale. The methods used in this research in the research conducted through two cycles of activity, and each cycles as much as 2 meeting. The subjek of this research is the teacher and all students of classes VII-B of 30 people. The object of this research are mathematical problem solving ability of students and the analysis undertaken aiming to find out the types of difficulties, hardships, cause factors and how the students in difficulty against handling problem solving math.